Comparison of individual characteristics of LTC residents in various forms of in-patient LTC in Poland - Wrotek, Małgorzata; Kalbarczyk, Małgorzata (Studia Demograficzne, 2025)
The ageing of the Polish population in the face of the decreasing caring potential of families is a challenge for the development of formal long-term care in the coming years. In order to be able to predict trends in the demand for care services better and thus reliably estimate future public expenditure of the sector, it is necessary to analyse the individual characteristics of beneficiaries using various forms of care. The aim of this article is to provide insight into the differences between residents of various forms of in-patient care for older adults and dependent people in Poland. The study has collected unique individual data on residents from private rest homes, public residential homes (in Polish: DPS), and public nursing homes (in Polish: ZOL) throughout Poland. Using statistical analysis, we show that people with smaller social networks and more limited financial resources are more likely to be in public residential homes. At the same time, they stay there longer and more often experience less ADL difficulties.